A Study of Physiological Signals-based Emotion Recognition Systems (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The use of physiological signals is relatively recent development in human emotion recognition. Interest in this field has been motivated by the unbiased nature of such signals, which are generated autonomously from the central nervous system. Generally, these signals can be collected from the cardiovascular system, respiratory system, electrodermal activities, muscular system and brain activities. This paper presents an overview of emotion recognition using physiological signals. The main components of a physiological signals-based emotion recognirion system are explained, including discussion regarding the concepts and problems about the various stages involved in its framework.